Rabi oscillation generation in the microring resonator system with double-series ring resonators - Ahmad Noorden, Ahmad Fakhrurrazi (Springer Verlag, 2015)
In this paper, a microring resonator (MRR) system using double-series ring resonators is proposed to generate and investigate the Rabi oscillations. The system is made up of silicon-on-insulator and attached to bus waveguide which is used as propagation and oscillation medium. The scattering matrix method is employed to determine the output signal intensity which acts as the input source between two-level Rabi oscillation states, where the increase of Rabi oscillation frequency with time is obtained at the resonant state. The population probability of the excited state is higher and unstable at the optical resonant state due to the nonlinear spontaneous emission process. The enhanced spontaneous emission can be managed by the atom (photon) excitation, which can be useful for atomic related sensors and single-photon source applications.